On a two point boundary value problem for linear differential equations of the fourth order in the colombeau algebra - Ligęza, Jan (Annales Mathematicae Silesianae, 2001)
The existence and uniqueness of solutions of the two point boundary value problem for ordinary linear differential equations of fourth order in the Colombeau algebra are considered.